DEVICES IMPACT ON THE CHILDERN: A SWOT ANALYSIS - Anna Sardiana (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The digital revolution has changed the culture of communication and people's behavior to move to media quickly and easily through the use of devices. This has an impact on school children as part of the community of mobile device users. This study wants to look at the impact of the use of devices on school children. The data in this study were obtained from various literatures which were processed and analyzed using SWOT analysis (strength, weakness, opportunity, threat). The results of the SWOT analysis in this study found that the use of devices in school children has positive and negative impacts and has opportunities and threats to watch out for. Keywords: devices, smartphone, gadget, SWOT analysis, digital native.